Regression analysis of the influence of auger surface hardness on its wear during dehydration of solid waste in a garbage truck - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O. (Problems of Tribology, 2021)
The article is dedicated to the study of the influence of the surface hardness of the auger on its wear during dehydration of solid waste in the garbage truck. Using the method of regression analysis, the logarithmic dependencies of auger wear depending on the hardness of its surface for different values of the friction path are determined. Graphical dependences of augur wear depending on the hardness of its surface for different values of the friction path are made up, and it confirms sufficient convergence of the obtained dependencies. Carried out additional regression analysis allowed to obtain the dependence of wear of the auger depending on the hardness of its surface and the friction path, which showed that during two weeks of operation and wear of the auger during dehydration of solid waste in the garbage truck increasing the surface hardness of the auger from 2310 MPa to 10050 MPa reducing the rate of growth of energy consumption of solid waste dehydration from 16.7 % to 1.5 %, and, consequently, to reduce the cost of the process of their dehydration in the garbage truck. The graphical dependence of the reduction of energy consumption of dehydration of solid household waste due to the increase in the hardness of the auger surface during its two-week wear is presented. It was established the expediency of further research to determine the rational material of the auger and ways to increase its wear resistance